A Series of Case Reports Regarding the Use of Massage Therapy to Improve Sleep Quality in Individuals with Post-Traumatic Stress Disorder (PTSD) - Sumpton, BScN, Bryn; Baskwill, PhD, MSc, BEd, RMT, Amanda (International Journal of Therapeutic Massage & Bodywork, 2019)
Background: Post-traumatic stress disorder (PTSD) is a common mental health diagnosis in Canada with prevalence estimated at about 2.4% in the general population. Previous studies have suggested massage therapy may be able to reduce the symptoms of PTSD. One of the symptoms commonly experienced is difficulty falling or staying asleep. No previously published massage therapy research has specifically assessed sleep symptoms of PTSD. Objectives: The research question was, “For individuals who have PTSD as a result of experiencing traumatic events, does MT have an effect on sleep quality?” Methods: A prospective series of case reports describing 10-week MT treatment plans provided by Registered Massage Therapists at Sutherland-Chan Clinic’s Belleville location. Three individuals with PTSD were recruited using promotional posters in the community. Treatment focused on improving sleep quality and followed a pragmatic treatment protocol using light to moderate pressure. Out-comes were measured using a sleep diary, Pittsburgh Sleep Quality Index, and the Leeds Sleep Evaluation Questionnaire. Results: Data collected at baseline and throughout the series showed inconsistent improvement and worsening of symptoms amongst participants. Treatment was well tolerated and attended. No harmful incidents were noted. Conclusion: For these participants, MT did not predictably impact sleep quality. It is possible, as the underlying cause of poor sleep quality was unlikely resolved, the participants did not have a significant change in their sleep quality. This differs from findings of previous studies in which MT improved sleep for patients with poor sleep quality due to exposure to traumatic events. There is need for further understanding of how MT affects sleep.